Duplex SYBR RT-qPCR for SARS-CoV-2 Detection in Malaysia: Duplex SYBR RT-qPCR for SARS-CoV-2 Detection in Malaysia - Mahali, Helyatul Rasmah; Amin, Zarina; Yusof, Nur Athirah (Journal of Tropical Life Science, 2025)
TaqMan probe-based commercial real-time PCR kits are the gold standard for COVID-19 diagnosis but are expensive. The large scale of SARS-CoV-2 infections necessitates affordable testing for humans, animals, and environmental samples. COVID-19 symptoms overlap with other respiratory infections like influenza, common cold, MERS, and SARS, requiring precise diagnostic tests such as real-time PCR. This study introduces a cost-effective method using melting curve analysis of a SYBR green multiplex assay with gel electrophoresis. We developed a duplex SYBR Green real-time PCR assay to detect the spike (S), envelope (E), RNA-dependent RNA polymerase (RdRp), and nucleocapsid (N) gene of SARS-CoV-2 using two sets of tubes. Specific primers were designed from conserved regions of the SARS-CoV-2 genome sequences isolated from Malaysia, retrieved from the GISAID database. Initial singleplex SYBR Green RT-PCR reactions for the N, E, S, and RdRp genes were optimized. After several rounds of optimization, we targeted the S and N genes in one tube and the E and RdRp genes in another. The assay uses real-time PCR to detect four genes with two primer sets distinguished by melting temperatures: 81.5°C and 88°C for the S and N genes, and 79.5°C and 85.5°C for the E and RdRp genes. It demonstrated high specificity and sensitivity, with a detection limit of 0.1 pg/μL of DNA. We compared this method to the LyteStar 2019-nCoV RT-PCR Kit (China), approved by Malaysia's Ministry of Health. Both kits accurately detected all positive SARS-CoV-2 samples without false positives. In conclusion, the newly developed duplex SYBR Green I-based real-time PCR assay demonstrates high sensitivity, specificity, and reliability, making it a valuable and effective alternative for the detection of SARS-CoV-2.